Morphological Innovations in Creole Languages: An Insight into Language Contact - Purnama, Yulian; Al-Mousaw, Zainab (Yayasan Adra Karima Hubbi, 2025)
Background. Creole language is a language that developed through contact between very different languages. Morphological innovations in these languages reflect dynamic adaptations to social and linguistic contexts. This study aims to explore morphological innovations in creole languages and how language contact plays a role in the formation of the language's morphological system. Purpose. The purpose of this study is to identify and analyze the types of morphological innovations in creole languages, as well as to examine the relationship between morphological changes and social and cognitive factors in the speaking community. Method. This study uses a qualitative approach with analysis of creole language morphological data obtained from interviews, daily conversations, and existing literature. The data were analyzed using descriptive and comparative methods to identify morphological innovation patterns. Results. The study found that reduplication was the most dominant morphological innovation in creole language, followed by new affixation and morphological borrowing. These innovations are largely influenced by social interaction and the influence of superstratum and substrate languages. Conclusion. Morphological innovations in creole languages demonstrate the ability of language to adapt and evolve despite having simple roots. This research contributes to a further understanding of how creole language evolved and served as a communication tool in complex social contexts.